Biosphere, Noosphere, and the Anthropocene: Earth's Perilous Prospects in a Cosmic Context. (16th November 2017) - Sideris, Lisa
Abstract : Visions of a high-tech 'good' Anthropocene as well as ambitious world-making projects like Biosphere 2 have roots in a quasi-religious form of cosmism and attendant notions of the noosphere: a planetary sphere of mind. Cosmic perspectives often celebrate and naturalize an image of humans as participants in and ultimately directors of planetary and cosmic processes. This brand of cosmism encourages fantasies of fleeing our 'used' planet in search of our presumed interstellar destiny, and it encourages a disregard of earthly, ecological, and even bodily limits. I argue that the turn to planetary and cosmic perspectives is the wrong move for those who care about the future of the Earth and more-than human life.